Kebijakan Pemerintah dalam Pendidikan dan Dinamika Bisnis Industri Penerbitan Buku Sekolah di Indonesia: Studi Kasus PT Tiga Serangkai - Eny Rahma Zaenah; Indah Susilowati; Deden Dinar Iskandar; Drajat Tri Kartono (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
This study aims to describe the record of events (event studies) related to government policies on education in Indonesia, especially those closely associated with the book publishing industry. In addition, there are also records of events that describe the dynamics of the school book publishing business at PT Tiga Serangkai in 20 (twenty) years, from 2001 to 2023. This timeline was chosen to provide a different description concerning digital transformation in the era of Industry 4.0. The researcher divides the timeline into the conventional phase, the transition phase, and the new era phase, where the COVID-19 pandemic phase becomes a transition point and acceleration of digital transformation that touches almost all life. The researcher uses a descriptive qualitative and quantitative approach. Data collection was carried out by studying documents related to government policies in the field of education during the study period of the above events, the study of company sales documents, and the study of documents from the Indonesian Publishers Association (IKAPI). Data deepening was carried out by structured interviews with informants who were selected purposively, especially related to data and information on business dynamics at PT. Tiga Serangkai. Data analysis was carried out in a qualitative descriptive manner. The results show that government policies significantly influence digital transformation in schools, both in learning and in the fulfillment of goods/services in education. In addition, government policies are closely related to school book publishing business innovation dynamics. On the other hand, the acceleration of digital transformation is greatly influenced by the COVID-19 pandemic.